Fatty acids composition and biohydrogenation reduction agents of tropical forages - MALIK MAKMUR; MARDIATI ZAIN; YETTI MARLIDA; KHASRAD KHASRAD; ANURAGA JAYANEGARA (Society for Indonesian Biodiversity, 2019)
Abstract. Makmur M, Zain M, Marlida Y, Khasrad, Jayanegara A. 2019. Fatty acids composition and biohydrogenation reduction agents of tropical forages. Biodiversitas 20: 1917-1922. The study was conducted to determine the composition of fatty acids, measured rumen biohydrogenation reduction agents (total phenols and total tannins) content and selected promising plants in various species of tropical forages. Ten species of tropical forages, namely, Panicum maximum, Cynodon plectostachyus, Pennisetum purpurephoides, Pennisetum purpureum, Brachiaria decumbens, Glyricidia sepium, Calliandra calothyrsus, Stylosanthes guaianensis, Leucaena leucocephala and Indigofera zollingeriana were used in this study. The fatty acids composition (% of total identified fatty acids) which were dominant in grasses were C18: 3n-3 (29%), C16: 0 (28%) and C18: 2n-6 (23%). Whereas in legumes, the significantly higher composition of fatty acids was C18: 3n-3 (42%) followed by C16: 0 (17%) and C18: 2n-6 (17%). The average poly-unsaturated fatty acids (PUFA) composition in grasses was relatively lower (44.6%) than legumes (59%). Likewise the content of total phenols and total tannins (g/100g DM) of grasses (0.91 and 0.41) and legumes (1.72 and 0.70). The selection of the forage plant species was based on the criteria of PUFA composition and biohydrogenation reduction agents using TOPSIS method. The results obtained show that B. decumbens (grass) and I. zollingeriana (legume) had the highest preference value of 0.74 and 0.87, respectively. In conclusion, B. decumbens and I. zollingeriana are forage species that have potential to provide healthier ruminant products.